(untitled) (Journal of Partial Differential Equations, 1990)
Concerning steady-state continuous casting problem, we know that if the number of phases is one, both existence and uniqueness had been solved ([1], [2], [3]), if the number of phases is two, the existence had been proved ([4]), but the uniqueness of weak solution is an open problem all the time. This paper is devoted to solving this problem.